Adnexal Mass with Surgical Treatment in Pregnant Women at Rajavithi Hospital: 2002-2005 - Ekachai Kovavisarach; Atchara Rit-hiran (The Royal Thai College of Obstetricians and Gynaecologists, 2009)
Objective: To analyse the incidence, histopathological diagnosis and pregnancy characteristics and outcomes of pregnant women undergone surgical treatment for adnexal mass at Rajavithi Hospital. Materials and Methods: A retrospective descriptive analysis database of pregnant women who underwent surgical treatment of adnexal mass during pregnancy in Department of Obstetrics and gynecologyin, Rajavithi Hospital between January 1st, 2001 and December 31st, 2005. Data collection included age, gravidity, parity, gestational age (at the time of surgery and delivery), histopathological diagnosis, maternal outcomes. Results: There were 66 pregnant women with adnexal masses that required surgical management among a total 45, 143 deliveries. The incidence of pregnant women with adnexal mass requiring surgical intervention in pregnancy was 1 in 684 deliveries. Of the 57 cases had complete data for analysis, 14 patients (24.56%) underwent emergency exploratory laparotomy, 43 patients (75.44%) underwent elective exploratory laparotomy before delivery. The two most common pathological findings were mature cystic teratoma (33.33%), endometrioma (17.54%). Only 2 malignant tumors or borderline malignant tumors (3.5%) were encountered: the first one was serous cystadenocarcinoma stage Ia and the other was borderline mucinous cystadenoma. There was only 1 preterm delivery (1.75%) in the elective surgery group. There were no any significant different between elective and emergency surgery groups in histopathological diagnosis, demographic characteristics and maternal outcomes. Conclusions. The incidence of pregnant women with adnexal mass requiring surgical intervention in pregnancy was 1 in 684 deliveries. The percentage of malignant tumor or tumor of low malignant potential was 3.5%. There were no any significant difference between elective and emergency surgery groups in histopathological diagnosis, demographic characteristics and maternal outcomes.